2003
DOI: 10.1128/iai.71.9.5381-5385.2003
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Systems of Helicobacter pylori Contribute to Virulence in a Mouse Infection Model

Abstract: Helicobacter pylori encodes three histidine kinases and five response regulators belonging to the family of two-component regulatory systems which are involved in transcriptional control. Here we demonstrate that isogenic mutants of H. pylori P76 with deletions of the response regulator open reading frame (ORF) HP1365 and ORFs HP244, HP165, and HP1364 encoding histidine kinases are unable to colonize the stomachs of BALB/c mice, suggesting an essential role of these systems in the regulation of important virul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…Protein samples estimated to be Ͼ95% pure were analyzed by NMR. 15 N-and 13 C, 15 N-labeled samples were produced by a process similar to that described above, but cells were grown in M9 medium with the addition of 13 C-labeled glucose and 15 Nlabeled ammonium chloride (CIL, Andover, MA).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Protein samples estimated to be Ͼ95% pure were analyzed by NMR. 15 N-and 13 C, 15 N-labeled samples were produced by a process similar to that described above, but cells were grown in M9 medium with the addition of 13 C-labeled glucose and 15 Nlabeled ammonium chloride (CIL, Andover, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Gel-shift and DNA-footprinting analyses have shown that ArsR binds directly to the promoter regions of these genes (17,18). Thus, the ArsRS TCS has an important role in allowing H. pylori to regulate gene expression in response to changes in pH and also has an important role in allowing H. pylori to colonize the gastric mucosa (15).…”
mentioning
confidence: 99%
See 3 more Smart Citations